Post-Divorce Experiences in Türkiye and the Social Structures Behind the Reasons for Divorce - Çağrı Elmas; Nurşen Adak (İstanbul Üniversitesi Sosyoloji Dergisi)
In developing countries such as Türkiye, traditional factors such as a patriarchy make the reasons for divorce unique. The causes and consequences of divorce include changes in economic conditions, the gender division of labor, and a rising tendency toward individualism over collectivism. Economic instability and lower living standards are not only a cause but an inevitable consequence of divorce, especially for women who face disproportionate financial difficulties, even after taking shared incomes into account. Gender differences and changes in social and economic conditions are the two main factors in the increase in divorce rates in Türkiye and around the world. This study aims to examine the similarities and clustering of reasons for divorce in terms of individuals’ gender, education, income, marital status, and region in Türkiye using a multiple correspondence analysis (MCA) based on the Family Structure in Türkiye (TAYA) 2021 dataset. The dataset includes information about the reasons for divorce from male and female participants over the age of 18 who have undergone divorce at least once. The results from the MCA analysis reveal both men and women to show a number of similar reasons for divorce, such as economic and family problems. However, gender-based variations are found regarding response intensities to these causes. While women tend to place more emphasis on such factors as emotional and domestic violence, men tend to be very home-oriented and to have expressed practical issues such as acceptance of their extended family’s views. The study also reveals socioeconomic factors such as income and education level to play an important role in shaping the reasons for divorce for both genders.